Using Secondary Data to Build Strong Extension Programs - Cheri Winton Brodeur; Glenn D. Israel; Diane D. Craig (EDIS, 2011)
In planning extension programming, collecting and analyzing information about client needs can be expensive and time consuming. This revised 4-page fact sheet describes the benefits and limitations of using secondary data, how to evaluate it, and ways to locate quality secondary data. Written by Cheri Winton Brodeur, Glenn D. Israel, and Diane D. Craig, and published by the UF Department of Agricultural Education and Communication, October 2011.